Risk factors for general complications after hip or knee replacement surgery in elderly patients: a single-center study - Huaxing Zhang; Jingjing Cao; Jia Chen; Xiaoran Ning (BMC Musculoskeletal Disorders, 2025)
Abstract Purpose To determine the risk factors for complications after hip or knee replacement surgery in elderly patients. Methods In total, 401 elderly patients (aged ≥ 65 years) who underwent hip or knee replacement surgery at a hospital from January 2017 to December 2022 were retrospectively analyzed. Univariate analysis was performed to identify significant variables. Risk factors and the effects of the model were examined by unconditional binary logistic regression analyses and receiver operating characteristic (ROC) curve analysis, respectively. Results A total of 122 (30.42%) patients were diagnosed with complications after hip or knee replacement surgery, and the independent risk factors for complications were age, body mass index (BMI) and hypertension. Fifty-six patients (13.97%) developed lower extremity venous thrombosis (LEVT), and the independent risk factors were hypertension, surgical joint type and visual analog scale (VAS) pain score. Cardiopulmonary complications occurred in 50 patients (12.47%), and the independent risk factors were age and BMI. Postoperative delirium occurred in 15 patients (3.74%), and its independent risk factors were age and American Society of Anesthesiologists (ASA) grade. Two or more complications occurred in 17 patients (4.24%), and the independent risk factors were age and diabetes. Conclusions This study focused on elderly patients with risk factors for complications after hip or knee replacement surgery. Clinically, elderly patients undergoing hip or knee replacement surgery should perform well in terms of preoperative and perioperative management.